2017
DOI: 10.3390/rs9020174
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Modelling using Satellite-Based Crop Coefficients: A Comparison of Methods at the Basin Scale

Abstract: Abstract:The parameterization of crop coefficients (kc) is critical for determining a water balance. We used satellite-based and literature-based methods to derive kc values for a distributed hydrologic model. We evaluated the impact of different kc parametrization methods on the water balance and simulated hydrologic response at the basin and sub-basin scale. The hydrological model SPHY was calibrated and validated for a period of 15 years for the upper Segura basin (~2500 km 2 ) in Spain, which is characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Allen et al (1998). Similarly, Hunink et al (2017) compared different applications of crop coefficients based on remotely sensed vegetation indices in hydrologic modelling. They found that the effect of crop coefficient parameterisations on the water balance is trivial and constant throughout the year; however, it has a major effect on seasonal evapotranspiration and soil moisture fluxes, showing the role of crop coefficients in spatial calibration.…”
Section: Distributed Root Fraction Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…Allen et al (1998). Similarly, Hunink et al (2017) compared different applications of crop coefficients based on remotely sensed vegetation indices in hydrologic modelling. They found that the effect of crop coefficient parameterisations on the water balance is trivial and constant throughout the year; however, it has a major effect on seasonal evapotranspiration and soil moisture fluxes, showing the role of crop coefficients in spatial calibration.…”
Section: Distributed Root Fraction Coefficientmentioning
confidence: 99%
“…Since AET cannot be measured directly by satellite, surface energy balance models are developed to estimate AET based on data from a range of spectral and thermal bands (Guzinski et al, 2013;Norman et al, 1995;Su, 2002). While these satellite-based estimates are usually employed as a tool to understand and improve the model parameterisations (Conradt et al, 2013;Hunink et al, 2017;Schuurmans et al, 2011), they can also be used to calibrate models (Crow et al, 2003;Immerzeel and Droogers, 2008;Zhang et al, 2009). Therefore, adding satellite-based observations to model calibration is not novel; however, specifically evaluating spatial patterns in the calibration has rarely been done (Stisen et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…For cultivated catchments, the growth of the vegetation often induces a non-stationarity of the hydrological behavior of the catchment, and consequently, of the model parameters [22,23]. Such variability requires to be related to a reliable descriptor of the growth of the vegetation.…”
Section: Normalized Difference Vegetation Indexmentioning
confidence: 99%
“…The Spatial Processes in Hydrology model (SPHY) was used to simulate each basin (Lutz et al, 2013(Lutz et al, , 2014Terink et al, 2015;Lutz et al, 2016;Hunink et al, 2017). SPHY is a spatially distributed conceptual hydrological model, including repre-…”
Section: Methods Model and Datamentioning
confidence: 99%